2008
DOI: 10.1002/syn.20527
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and biochemical correlates of the dyskinetic potential of dopaminergic agonists in the 6‐OHDA lesioned rat

Abstract: Prolonged treatment with L-DOPA induces highly disabling dyskinesia in Parkinson's disease (PD) patients. In contrast, dopaminergic agonists display variably dyskinetic outcome, depending on pharmacokinetic/pharmacodynamic profile. The present study was aimed at assessing behavioral and biochemical correlates of intense or mild dyskinesia displayed by the different dopamine (DA) receptors stimulation in a rat model of PD. The effect of subchronic stimulation of the D(1) receptor by SKF38393, and the D(2)/D(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 62 publications
5
20
0
Order By: Relevance
“…To this regard, the finding that subchronic administration of MP extract, in contrast to subchronic L-DOPA, induced sensitization of contralateral turning behavior but not sensitization of AIMs which were of low intensity and stable throughout the duration of treatment, is of particular interest. Previous results have shown that drugs owing low dyskinetic potential such as bromocriptine or ropinirole induce sensitization in contralateral turning behavior, not associated to sensitization in AIMs (Henry et al 1998;Ravenscroft et al 2004;Carta et al 2008). On the contrary, drugs such as L-DOPA owing high dyskinetic potential induced sensitization in AIMs after repeated treatment (Lundblad et al 2002;Pinna et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…To this regard, the finding that subchronic administration of MP extract, in contrast to subchronic L-DOPA, induced sensitization of contralateral turning behavior but not sensitization of AIMs which were of low intensity and stable throughout the duration of treatment, is of particular interest. Previous results have shown that drugs owing low dyskinetic potential such as bromocriptine or ropinirole induce sensitization in contralateral turning behavior, not associated to sensitization in AIMs (Henry et al 1998;Ravenscroft et al 2004;Carta et al 2008). On the contrary, drugs such as L-DOPA owing high dyskinetic potential induced sensitization in AIMs after repeated treatment (Lundblad et al 2002;Pinna et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Serotonergic activation at dorsal/medial raphé and terminal receptors is sufficient to reduce LID (Carta et al, 2008), brought about by an increase in extracellular monoamine levels, reducing the synaptic release of glutamate and 5-HT and controlling dysregulated release. Under these principles AIM reduction in response to amphetamine, as shown in this study, is likely to be a through a combined modulation of grafted 5-HT neurones, host 5-HT terminals and corticostriatal connections.…”
Section: Discussionmentioning
confidence: 99%
“…DA D 1 receptor (D 1 R) agonists are more efficient than D 2 R agonists to induce dyskinesia in animal models and PD patients (Calon et al, 1999;Rascol et al, 2001Rascol et al, , 2006Carta et al, 2008). D 1 Rs are necessary for LID development (Westin et al, 2007;Darmopil et al, 2009).…”
Section: Introductionmentioning
confidence: 99%